The Kidney Transplant Evaluation Process in the Elderly: Reasons for Being Turned down and Opportunities to Improve Cost-Effectiveness in a Single Center - Beatrice P. Concepcion; Rachel C. Forbes; Aihua Bian; Heidi M. Schaefer (Journal of Transplantation)
Background. The kidney transplant evaluation process for older candidates is complex due to the presence of multiple comorbid conditions. Methods. We retrospectively reviewed patients ≥60 years referred to our center for kidney transplantation over a 3-year period. Variables were collected to identify reasons for patients being turned down and to determine the number of unnecessary tests performed. Statistical analysis was performed to estimate the association between clinical predictors and listing status. Results. 345 patients were included in the statistical analysis. 31.6% of patients were turned down: 44% due to coronary artery disease (CAD), peripheral vascular disease (PVD), or both. After adjustment for patient demographics and comorbid conditions, history of CAD, PVD, or both (OR = 1.75, 95% CI (1.20, 2.56), p=0.004), chronic obstructive pulmonary disease (OR = 8.75, 95% CI (2.81, 27.20), p=0.0002), and cancer (OR 2.59, 95% CI (1.18, 5.67), p=0.02) were associated with a higher risk of being turned down. 14.8% of patients underwent unnecessary basic testing and 9.6% underwent unnecessary supplementary testing with the charges over a 3-year period estimated at $304,337. Conclusion. A significant number of older candidates are deemed unacceptable for kidney transplantation with primary reasons cited as CAD and PVD. The overall burden of unnecessary testing is substantial and potentially avoidable.